Molecular mechanisms of neutrophil regulatory network in anti-Candida infection - Xu, Yanhua; Cheng, Renyi; Li, Wen; Yu, Wenjing; Chen, Chider (Frontiers in Immunology, 2025)
Candida albicans resides as a commensal within the oral mucosa but becomes pathogenic when epithelial or immune equilibrium collapses. Neutrophils constitute the dominant effector population controlling this transition, integrating pathogen- and host-derived cues into a coordinated antimicrobial program. Fungal β-glucan recognition through Dectin-1 and complement receptor 3 (CR3) activates spleen tyrosine kinase (SYK)–phosphoinositide 3-kinase (PI3K)–extracellular signal-regulated kinase (ERK) pathways and drives microtubule-associated protein 1 light chain 3B-II (LC3B-II) accumulation and NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome assembly, thereby coupling phagocytosis with oxidative burst and neutrophil extracellular trap (NET) formation. Caspase recruitment domain-containing protein 9 (CARD9)-dependent interleukin (IL)-17 and tumor necrosis factor-α (TNF-α) circuits sustain chemokine (C-X-C motif) ligand 1/2 (CXCL1/2)-directed neutrophil recruitment and granulocyte colony-stimulating factor (G-CSF)-mediated granulopoiesis, while tissue matrix components determine site-specific antigen handling and NETosis thresholds. Hypha-restricted peptide toxin Candidalysin links epithelial injury to NLRP3 activation and release of IL-1β, IL-6, and G-CSF, establishing an oropharyngeal candidiasis (OPC)-specific neutrophil regulatory loop critical for pathogen clearance but also for mucosal inflammation. Conversely, fungal morphogenesis, biofilm organization, and metabolic rewiring dampen reactive oxygen species (ROS) generation and promote immune tolerance and drug resistance. Clinically, G-/granulocyte-macrophage colony-stimulating factor (GM-CSF) adjuvants and G-CSF-mobilized granulocyte transfusion offer context-dependent benefits yet pose toxicity risks, underscoring the need for precise intervention in neutrophil activation. Advances in single-cell and spatial multi-omics approaches are uncovering the metabolic and functional heterogeneity of neutrophils within mucosal environments, providing mechanistic insight for targeted immunomodulation.